Clinical Impact of Antecedent Bariatric Surgery on Liver Transplant Outcomes: A Retrospective Matched Case-control Study. Issue 6 (June 2021) - Serrano, Oscar K.; Peterson, Kent J.; Vock, David M.; Berglund, Danielle; Kandaswamy, Raja; Lake, John R.; Pruett, Timothy L.; Chinnakotla, Srinath
Abstract : Background: Bariatric surgery (BS) may be associated with significant malabsorption and nutritional deficiencies. Methods: Between March 1987 and January 2017, we performed 922 liver transplants (LT) at our institution; 33 had antecedent BS. We matched the BS cohort to LT recipients without BS (1:3 matching) based on exact matching for gender and cancer and inverse variance matching for age, LT body mass index, MELD score, and transplant date. Results: We analyzed outcomes in 132 LT recipients (33 BS; 99 non-BS). The BS cohort comprised 26 (79%) women with a mean age of 52.4 years. The BS procedures included 20 Roux-en-Y gastric bypass (61%), 6 jejunoileal bypass (18%), 3 gastric band (9%), 2 sleeve gastrectomy (6%), and 1 duodenal switch (3%). The primary indications for LT listing were alcoholic cirrhosis (9; 27%), nonalcoholic steatohepatitis (7; 21%), hepatitis C (8; 24%), and hepatocellular carcinoma (3; 9%). At LT, body mass index for the BS cohort was 29.6, and MELD was 24. Compared with matched controls, BS recipients did not have longer LT length of hospital stay (17.8 versus 15.7 d, P = 0.71), longer intensive care unit length of stay (5.3 versus 4.1 d, P = 0.16), or higher 30-day complication rate (76% versus 85%, P = 0.43). Overall patient survival was similar (1- and 3-y survival was 90.1% and 75.9% for BS; 90.9% and 76.4% for non-BS, P = 0.34). Conclusions: A history of BS does not portend a deleterious effect on LT outcomes.